A ANALISIS PEMAHAMAN DAN KESIAPAN PELAKU USAHA MIKRO KECIL DAN MENENGAH (UMKM) DALAM IMPLEMENTASI SAK EMKM - Ghina Salsa Bila (Jurnal Ilmu Akuntansi, 2023)
This study aims to determine of understanding and readiness of Micro, Small and Medium Enterprises (MSMEs) actors in Sukabumi City in implementing SAK EMKM. This study used a qualitative method with a descriptive approach using 5 informants as MSME owners in the city of Sukabumi. The data obtained are in the form of primary data obtained through interviews, as well as secondary data from books, library literature, documentation and journals. Based on the results of the discussion, it can be concluded that the application of accounting records in MSMEs has been implemented by MSME owners even with simple recording. Most of the MSME informants have implemented the concept of a business entity by separating business assets and personal assets. However, for applying the accrual basis in MSMEs, it cannot be implemented. MSME owners always record transactions when receiving and issuing cash and very minimal knowledge about SAK EMKM due to the absence of socialization from related parties.